Sensibilização cruzada entre anfetamina e nicotina: avaliação neuroquímica do núcleo acumbens e córtex préfrontal em ratos adolescentes e adultos - Oliveira, Paulo Eduardo Carneiro de (2009)
Nicotine and psychostimulants are often abused in combination. Drug abuse often begins during adolescence. Exposure to drugs of abuse during adolescence can have long-term consequences. We have previously demonstrated that adolescent rats pretreated with amphetamine displayed behavioral sensitization to nicotine, which persisted until adulthood. Moreover, the pretreatment with nicotine during adolescence sensitized adolescent and adult animals to amphetamine-induced locomotor activation. In the present study we investigated whether the behavioral cross-sensitization between nicotine and amphetamine is related to changes in dopamine or serotonin neurotransmission. To this end adolescent rats (post-natal day 28) were treated with nicotine (0.4 mg/Kg), amphetamine (5.0 mg/Kg) or saline during seven days. Three or thirty days after the last injection animals received an acute injection of nicotine (0.4 mg/Kg), amphetamine (5.0 mg/Kg for adolescents or 1.0 mg/Kg for adults) or saline. Thirty minutes after challenge rats were sacrificed, decapitated and brains removed. Nucleus accumbens (NAcc) and prefrontal cortex (PFC) were dissected and prepared for HPLC (high performance liquid chromatography) analysis. Dopamine, DOPAC, HVA, serotonin and 5-HIAA were measured in these brain regions. Our results showed that: 1) repeated administration of nicotine attenuated the acute effect of amphetamine on NAcc dopamine levels of adolescent rats; 2) repeated administration of nicotine increased the acute effect of amphetamine on PFC dopamine levels of adolescent rats; 3) repeated administration of nicotine, during adolescence, increased the acute effect of amphetamine on PFC dopamine of adult rats. The behavioral cross-sensitization shown previously is not related to alterations in NAcc and PFC concentrations of neurotransmitters and its metabolites. However, neuroadaptations induced by repeated nicotine during adolescence endures until adulthood.